Teachers’ Strategies in Using Canva Media in Aqidah Akhlak Learning to Increase Students’ Learning Interest - Yonani, Sarmi; Khermarinah, Khermarinah; Aryati, Aziza (Journal of Educational Sciences, 2025)
This study aims to explore teachers’ strategies in utilizing Canva media in Aqidah Akhlak learning and to identify the supporting and inhibiting factors affecting its implementation. The integration of digital media, particularly Canva, represents an innovative effort to enhance students’ interest and engagement in learning moral and theological content. This research was conducted in the context of Islamic education, where the application of creative digital tools remains limited. Employing a descriptive qualitative approach, data were collected through interviews, classroom observations, and documentation. The analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that teachers implemented several strategies in using Canva, such as selecting engaging templates, integrating multimedia elements, adjusting content to the digital format, combining Canva with conventional methods, and conducting reflective evaluations. Supporting factors included teachers’ prior training, administrative support, sufficient internet access, and students’ enthusiasm. Meanwhile, inhibiting factors involved limited technological infrastructure and the cost of Canva Pro features. In conclusion, the integration of Canva media into Aqidah Akhlak learning can effectively foster students’ learning motivation and creativity when supported by adequate facilities and institutional commitment.